Molecular Detection and Characterization of Rickettsia Species in Ixodid Ticks Collected From Cattle in Southern Zambia - Chitanga, Simbarashe; Chibesa, Kennedy; Sichibalo, Karen; Mubemba, Benjamin; Nalubamba, King S.; Muleya, Walter; Changula, Katendi; Simulundu, Edgar (Frontiers in Veterinary Science, 2021)
Tick-borne zoonotic pathogens are increasingly becoming important across the world. In sub-Saharan Africa, tick-borne pathogens identified include viruses, bacteria and protozoa, with Rickettsia being the most frequently reported. This study was conducted to screen and identify Rickettsia species in ticks (Family Ixodidae) infesting livestock in selected districts of southern Zambia. A total of 236 ticks from three different genera (Amblyomma, Hyalomma, and Rhipicephalus) were collected over 14 months (May 2018–July 2019) and were subsequently screened for the presence of Rickettsia pathogens based on PCR amplification targeting the outer membrane protein B (ompB). An overall Rickettsia prevalence of 18.6% (44/236) was recorded. Multi-locus sequencing and phylogenetic characterization based on the ompB, ompA, 16S rRNA and citrate synthase (gltA) genes revealed the presence of Rickettsia africae (R. africae), R. aeschlimannii-like species and unidentified Rickettsia species. While R. aeschlimannii-like species are being reported for the first time in Zambia, R. africae has been reported previously, with our results showing a wider distribution of the bacteria in the country. Our study reveals the potential risk of human infection by zoonotic Rickettsia species and highlights the need for increased awareness of these infections in Zambia's public health systems.